Law Enforcement Against Mass Shootings in United States - Zulaeka, Cindy Atika; Prastyanti, Rina Arum (MultiTech Publisher, 2024)
The occurrence of mass shootings in the United States is a major issue due to its complexity and controversy, representing a serious problem or incident. In this study, we investigate the challenges faced by law enforcement in handling mass shootings, including interagency coordination and risk management for societal security. We analyze various policy approaches taken to enhance law enforcement effectiveness in preventing and reform efforts needed to prevent similar incidents in the future, addressing gun laws and solutions to response to mass shootings. A review of literature methods and case studies that will present a research approach using wrriten sources such as journals, books, articles, and other documents as a basis for compiling, analyzing, synthesizing knowledge and data on identifying cases of mass shootings in the United States or a specific case.